Peningkatan Pengetahuan Latihan Keseimbangan untuk Mengurangi Resiko Jatuh pada Lanjut Usia - Purwantini, Dwi; Prasetya, Arief Widya; Saputra, Agung Kurniawan (Jurnal Abdimas Kesehatan (JAK), 2024)
The elderly at the Rosan Kemuning posyandu experience problems with dynamic balance, poor coordination and agility. This problem increases the risk of falls and reduces independence. Dynamic balance is important for maintaining postural stability during movement. Objective: increase awareness of health and knowledge of elderly people at Posyandu Rosan Kemuning RW III, Kelurahan Kebraon, Kecamatan Karangpilang regarding balance training. Methods: used were lectures, leaflets and questions and answers. A total of 38 elderly people consisting of elderly women, men and elderly posyandu cadres participated in this activity. Results: there was an increase in behavioral aspects in knowledge about balance training increased by 100%, knowledge about good balance will reduce the risk of falls increased by 100%, knowledge about balance training can strengthen leg muscles increased by 95%, knowledge about balance training can increase independence increased 100%, and knowledge of balance exercise dosage increased 92%. Based on the results of community service, it can be concluded that Health Education is very effective in increasing knowledge and awareness of Health